(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In order to identify good ethical practices for justices/judges we may considerwhat constitutes a role model judge (“Good Judge”). First, it is necessary to point out that it is not only a matter of normative; we can’t reduce ethics for justices to alist of duties and rights. A “good judge” must also be someone who develops professionally the necessary virtues required in order to perform his or her function well (judicial virtues). A “good Judge” is independent and impartial carrying out his function, and judge with prudence (according with the facts and the Law). He or she has social conscience and ongoing commitment to furthering his or her knowledge. A Good Judge is held in high esteem by the lawyers and people who work under him orher, and is aware not only about the dignity of his Job but also that he or she has toserve to the society with the spirit of sacrifice.